Konsep Pemberian Upah Terhadap Tenaga Kerja/Buruh Menurut Perspektif Islam - Fahmi Ardiansyah Siregar; Hafiz Wahyu Wijaya Marpaung; Afrillia; Nabila Izmi Aina (ITB Ahmad Dahlan Jakarta, 2023)
A worker is a worker who works for another person by fulfilling his duties and obligations as an employee for the purpose of getting a wage commensurate with what he does in accordance with a predetermined collective agreement. In the case of giving wages, an employer may not deliberately default on his obligation to pay his employees, which in addition to violating the employment contract is also contrary to the principles of justice in Islam. Justice is seen from the accuracy of employers in giving wages to workers. The type of research used in this research is literature review research which results from the analysis of various conceptual information as well as qualitative and quantitative data from various previously published scientific articles. The results of this study are that Islam provides guidelines to parties who provide jobs to others that remuneration must include two things, namely fair and sufficient. Justice is seen from the accuracy of the employers in giving wages to workers, and can also be seen from the proportionality of the level of employment with the amount of wages they receive.